Studi Penjaminan Mutu (Quality Assurance) Dalam Pelayanan Kefarmasian di Apotek - Nurchamidin Gobel; Teti S. Tuloli; Madania Madania (Journal Syifa Sciences and Clinical Research, 2022)
Low Quality Assurance in Pharmacy Award Ipilo Gorontalo include pharmaceutical, security, procurement, storage, and distribution or drug delivery, drug management, on a prescription drug services, drug information services, as well as drug development, medicinal materials and traditional medicine. The impact of the implementation of activities in the pharmacy pharmacy services Anugerah Ipilo errors may occur treatment (medication errors) in the service process. Quality Assurance (QA) is one dimension that is used in the measurement of quality of service, where the application of QA in pharmacies Ipilo Award aims to provide quality assurance of pharmaceutical products and the quality of services provided to patients. This research is descriptive, the source of primary data obtained from the questionnaires with QA standard indicator framework on pharmaceutical services in pharmacies Anugerah Ipilo. The assessment results then classified based on criteria appropriate, relatively appropriate and not appropriate. The results showed that the Quality Assurance (Quality Assurance) on the quality of the equipment and the safety assurance of Pharmaceutical Services in Pharmacy Award Ipilo there are seven questions (70%) had a very good criteria, three questions (30%) had a good criterion. Quality Assurance (Quality Assurance) on the Process of Pharmaceutical Services in Pharmacy Award Ipilo there are 4 questions (40%) had a very good criteria, one question (10%) had a pretty good and 5 questions (50%) had less good. Pharmacies merely focused on the administration and management of medication alone is not the overall pharmacy services, in addition because the pharmacy Anugerah Ipilo prefer the function of the economy (business) rather than its social function, which pharmacies are required to gain / profit in business.